Towards an analysis of contemporary sport: the proposition of a model - Marchi Júnior, Wanderley (Revista da ALESDE, 2025)
This essay is grounded in conceptual reflections on sport developed within the scientific field—particularly in the sociology of sport—as well as in the enduring notions of sport constructed in society. Based on this, the essay aims to present a proposal for understanding sport through an analytical model that enables to interpret its caracheteristics in the contemporary context. This model is composed of five dimensions: emotion, esthetics, ethics, entertainment, and education. The analytical model we propose serves as a tool that may contribute to the analysis of sport in contemporary times, avoiding a restricted understanding centered on biological and health-related aspects, as is often observed in physical education programs. In this way, the model broadens the interpretative horizon of sport, offering theoretical foundations for contemporary socio-cultural analyses.